2011
DOI: 10.1016/j.jvs.2010.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients undergoing endovascular infrainguinal interventions with single-vessel peroneal artery runoff

Abstract: Patients with PAOR have similar long-term outcomes to patients with non-PAOR. Thus, infrainguinal endovascular revascularization can be considered a first-line therapy for patients with PAOR and critical limb ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The angiosome model holds that the areas supplied by the PEA are the anterior and lateral ankle and plantar heel 30 . However increasingly the PEA has been shown to have multiple collaterals and to commonly supply the pedal arteries and as such has comparable outcomes for both surgical and endovascular revascularisation compared to other distal target vessels [31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…The angiosome model holds that the areas supplied by the PEA are the anterior and lateral ankle and plantar heel 30 . However increasingly the PEA has been shown to have multiple collaterals and to commonly supply the pedal arteries and as such has comparable outcomes for both surgical and endovascular revascularisation compared to other distal target vessels [31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are studies that demonstrate comparable outcomes to those with single tibial vessel run off for both bypass and endovascular intervention. 14,15 The results demonstrated that patients in both groups had a similar degree of disease in the pedal vessels. In the literature, this has been an inconsistent finding 11e13, 16,17 and the influence of chronic kidney disease may be partly responsible for this.…”
Section: Discussionmentioning
confidence: 85%
“…19e21 In addition to that patients with pedal disease have been found to have higher rates of amputation and mortality and it is an independent predictor of failure of revascularisation. 22 The difficulty with classification systems that consider the burden of arterial disease is relating the severity of .45 Anterior tibial, proximal 3rd 2 (13) 4 (13) .078 Anterior tibial, middle 3rd 0 (15) 3 (15) .17 Anterior tibial, distal 3rd 3 (15) 13 (15) .12 Dorsalis pedis 4 (15) 13 (15) .31 Peroneal, proximal 3rd 0 (4) 1 (6) .40 Peroneal, middle 3rd 0 (7) 0 (13) .29 Peroneal, distal 3rd 0 (13) 0 (15) .55 Posterior tibial, proximal 3rd 0 (13) 3 (15) .038 Posterior tibial, middle 3rd 2 (15) 3 (15) .17 visualised disease to the clinical picture and treatment outcomes. The global vascular guidelines on the management of chronic limb threatening ischaemia published in 2019 have tried to address this.…”
Section: Discussionmentioning
confidence: 99%
“…No studies to date have specifically described the patency rates of peroneal artery endovascular interventions in a cohort of patients with an isolated peroneal artery runoff. Two studies, however, have compared the outcomes after infrainguinal intervention in patients with peroneal artery-only runoff to those with other runoff 15,16 . A large fraction of patients in both studies underwent isolated femoropopliteal interventions, and thus their patency rates cannot be compared to ours; however, both groups of investigators concluded that isolated peroneal runoff by itself does not negatively affect outcomes after revascularization.…”
Section: Discussionmentioning
confidence: 99%